Smad7:β-catenin complex regulates myogenic gene transcription - Tripathi, Soma (Cell Death Dis, 2019)
Recent reports indicate that Smad7 promotes skeletal muscle differentiation and growth. We previously documented a non-canonical role of nuclear Smad7 during myogenesis, independent of its role in TGF-β signaling. Here further characterization of the myogenic function of Smad7 revealed β-catenin as a Smad7 interacting protein. Biochemical analysis identified a Smad7 interaction domain (SID) between aa575 and aa683 of β-catenin. Reporter gene analysis and chromatin immunoprecipitation demonstrated that Smad7 and β-catenin are cooperatively recruited to the extensively characterized ckm promoter proximal region to facilitate its muscle restricted transcriptional activation in myogenic cells. Depletion of endogenous Smad7 and β-catenin in muscle cells reduced ckm promoter activity indicating their role during myogenesis. Deletion of the β-catenin SID substantially reduced the effect of Smad7 on the ckm promoter and exogenous expression of SID abolished β-catenin function, indicating that SID functions as a trans dominant-negative regulator of β-catenin activity. β-catenin interaction with the Mediator kinase complex through its Med12 subunit led us to identify MED13 as an additional Smad7-binding partner. Collectively, these studies document a novel function of a Smad7-MED12/13-β-catenin complex at the ckm locus, indicating a key role of this complex in the program of myogenic gene expression underlying skeletal muscle development and regeneration.